Facilitating lean implementation through change management - Al Manei, Mohammed; Kaur, Rashmeet; Patsavellas, John; Salonitis, Konstantinos (Elsevier, 2024)
Implementing lean manufacturing can be challenging and requires all stakeholders to be engaged. Several frameworks have been presented in the last decades, with most of them being conceptual and failing to consider that change inertia exists. In the present paper, a social change management model is used to develop a lean implementation framework, with each step prescribed for the practitioners. The elements of the model are selected after a series of workshops, a thorough literature review, and the development of an interpretive structural model for this reason. The model was validated through experts’ opinions and presents an alternative approach to the established lean implementation roadmaps available in the literature.
Keywords: 4014 Manufacturing engineering; Lean Manufacturing; Lean Implementation; Change Management; ISM; Implementaiton design